Near-Threshold Cross Sections for Electron and Positron Impact Ionization of Atomic Hydrogen - Bray, Igor; Bray, A.; Fursa, Dmitry; Kadyrov, Alisher (The American Physical Society, 2018)
Using classical arguments Wannier [Phys. Rev. 90, 817 (1953)PHRVAO0031-899X10.1103/PhysRev.90.817] proposed an electron-impact ionization cross section for neutral atoms to behave as E1.127, where E is the excess energy above threshold. Using similar arguments Klar [J. Phys. B 14, 4165 (1981)JPAMA40022-370010.1088/0022-3700/14/21/027] obtained E2.65 to be the corresponding threshold law for positron impact. Recently, Babij et al. [Phys. Rev. Lett. 120, 113401 (2018)PRLTAO0031-900710.1103/PhysRevLett.120.113401] measured near-threshold positron-impact breakup behavior to be similar to that expected for electrons. Using the convergent close-coupling method for the atomic hydrogen target, we examine cross sections at near-threshold energies for electron and positron impact. Contrary to the experiment, the calculated cross sections are found to behave differently for the two projectiles and consistently with the aforementioned threshold laws, despite the entirely quantum nature of these problems. For electron impact, the threshold behavior holds while the total electron spin asymmetry remains constant, whereas for positron scattering the threshold law holds for breakup while the positronium-formation component of the ionization cross section remains constant.